Bioremediation Of Chlorpyrifos By Bacteria Isolated From The Cultivated Soils - SUMIT KUMAR (International Journal of Pharma and Bio Sciences, 2011)
In this study, chlorpyrifos degrading capability of four bacterial monocultures (RCC-2, GCC-1, GCC-3 and JCC-3) and two bacterial mixed-cultures (GCE345 and GCC134) was investigated in terms of treatment duration and culture volume, using soil slurry medium. Among the bacterial mono-cultures, RCC-2 was found to be most efficient with 21, 37, 54 and 77% of chlorpyrifos degradation in 5, 10, 15 and 30 days of treatment duration, respectively. Out of two bacterial mixed-cultures, GCC134 was more effective and resulted in 24, 38, 56 and 85% degradation of chlorpyrifos in 5, 10, 15 and 30 days of treatment, respectively. Chlorpyrifos degradation was higher by increasing the culture volume of respective bacterial cultures, from 10% to 25% (v/v), for 10 days of treatment at room temperature. The Pearson correlation between treatment duration and % degradation of chlorpyrifos were 0.953 and 0.988 with bacterial mono- and mixed-cultures, respectively.